Jordan Algebras¶
AUTHORS:
Travis Scrimshaw (2014-04-02): initial version
Travis Scrimshaw (2023-05-09): added the 27 dimensional exceptional Jordan algebra
- class sage.algebras.jordan_algebra.ExceptionalJordanAlgebra(O)[source]¶
Bases:
JordanAlgebra
The exceptional \(27\) dimensional Jordan algebra as self-adjoint \(3 \times 3\) matrix over an octonion algebra.
Let \(\mathbf{O}\) be the
OctonionAlgebra
over a commutative ring \(R\) of characteristic not equal to \(2\). The exceptional Jordan algebra \(\mathfrak{h}_3(\mathbf{O})\) is a \(27\) dimensional free \(R\)-module spanned by the matrices\[\begin{split}\begin{bmatrix} \alpha & x & y \\ x^* & \beta & z \\ y^* & z^* & \gamma \end{bmatrix}\end{split}\]for \(\alpha, \beta, \gamma \in R\) and \(x, y, z \in \mathbf{O}\), with multiplication given by the usual symmetrizer operation \(X \circ Y = \frac{1}{2}(XY + YX)\).
These are also known as Albert algebras due to the work of Abraham Adrian Albert on these algebras over \(\RR\).
EXAMPLES:
We construct an exceptional Jordan algebra over \(\QQ\) and perform some basic computations:
sage: O = OctonionAlgebra(QQ) sage: J = JordanAlgebra(O) sage: gens = J.gens() sage: gens[1] [0 0 0] [0 1 0] [0 0 0] sage: gens[3] [0 1 0] [1 0 0] [0 0 0] sage: gens[1] * gens[3] [ 0 1/2 0] [1/2 0 0] [ 0 0 0]
>>> from sage.all import * >>> O = OctonionAlgebra(QQ) >>> J = JordanAlgebra(O) >>> gens = J.gens() >>> gens[Integer(1)] [0 0 0] [0 1 0] [0 0 0] >>> gens[Integer(3)] [0 1 0] [1 0 0] [0 0 0] >>> gens[Integer(1)] * gens[Integer(3)] [ 0 1/2 0] [1/2 0 0] [ 0 0 0]
The Lie algebra of derivations of the exceptional Jordan algebra is isomorphic to the simple Lie algebra of type \(F_4\). We verify that we the derivation module has the correct dimension:
sage: len(J.derivations_basis()) # long time 52 sage: LieAlgebra(QQ, cartan_type='F4').dimension() 52
>>> from sage.all import * >>> len(J.derivations_basis()) # long time 52 >>> LieAlgebra(QQ, cartan_type='F4').dimension() 52
REFERENCES:
- class Element(parent, data)[source]¶
Bases:
AlgebraElement
An element of an exceptional Jordan algebra.
- monomial_coefficients(copy=True)[source]¶
Return a dictionary whose keys are indices of basis elements in the support of
self
and whose values are the corresponding coefficients.INPUT:
copy
– ignored
EXAMPLES:
sage: O = OctonionAlgebra(QQ) sage: J = JordanAlgebra(O) sage: elt = sum(~QQ(ind) * b for ind, b in enumerate(J.basis()[::6], start=1)); elt [ 1 1/2*k 1/3*i + 1/4*lk] [ -1/2*k 0 1/5*li] [-1/3*i - 1/4*lk -1/5*li 0] sage: elt.monomial_coefficients() {0: 1, 6: 1/2, 12: 1/3, 18: 1/4, 24: 1/5}
>>> from sage.all import * >>> O = OctonionAlgebra(QQ) >>> J = JordanAlgebra(O) >>> elt = sum(~QQ(ind) * b for ind, b in enumerate(J.basis()[::Integer(6)], start=Integer(1))); elt [ 1 1/2*k 1/3*i + 1/4*lk] [ -1/2*k 0 1/5*li] [-1/3*i - 1/4*lk -1/5*li 0] >>> elt.monomial_coefficients() {0: 1, 6: 1/2, 12: 1/3, 18: 1/4, 24: 1/5}
- algebra_generators()[source]¶
Return a basis of
self
.EXAMPLES:
sage: O = OctonionAlgebra(QQ) sage: J = JordanAlgebra(O) sage: B = J.basis() sage: B[::6] ([1 0 0] [0 0 0] [0 0 0], [ 0 k 0] [-k 0 0] [ 0 0 0], [ 0 0 i] [ 0 0 0] [-i 0 0], [ 0 0 lk] [ 0 0 0] [-lk 0 0], [ 0 0 0] [ 0 0 li] [ 0 -li 0]) sage: len(B) 27
>>> from sage.all import * >>> O = OctonionAlgebra(QQ) >>> J = JordanAlgebra(O) >>> B = J.basis() >>> B[::Integer(6)] ([1 0 0] [0 0 0] [0 0 0], [ 0 k 0] [-k 0 0] [ 0 0 0], [ 0 0 i] [ 0 0 0] [-i 0 0], [ 0 0 lk] [ 0 0 0] [-lk 0 0], [ 0 0 0] [ 0 0 li] [ 0 -li 0]) >>> len(B) 27
- basis()[source]¶
Return a basis of
self
.EXAMPLES:
sage: O = OctonionAlgebra(QQ) sage: J = JordanAlgebra(O) sage: B = J.basis() sage: B[::6] ([1 0 0] [0 0 0] [0 0 0], [ 0 k 0] [-k 0 0] [ 0 0 0], [ 0 0 i] [ 0 0 0] [-i 0 0], [ 0 0 lk] [ 0 0 0] [-lk 0 0], [ 0 0 0] [ 0 0 li] [ 0 -li 0]) sage: len(B) 27
>>> from sage.all import * >>> O = OctonionAlgebra(QQ) >>> J = JordanAlgebra(O) >>> B = J.basis() >>> B[::Integer(6)] ([1 0 0] [0 0 0] [0 0 0], [ 0 k 0] [-k 0 0] [ 0 0 0], [ 0 0 i] [ 0 0 0] [-i 0 0], [ 0 0 lk] [ 0 0 0] [-lk 0 0], [ 0 0 0] [ 0 0 li] [ 0 -li 0]) >>> len(B) 27
- gens()[source]¶
Return the generators of
self
.EXAMPLES:
sage: O = OctonionAlgebra(QQ) sage: J = JordanAlgebra(O) sage: G = J.gens() sage: G[0] [1 0 0] [0 0 0] [0 0 0] sage: G[5] [ 0 j 0] [-j 0 0] [ 0 0 0] sage: G[22] [ 0 0 0] [ 0 0 k] [ 0 -k 0]
>>> from sage.all import * >>> O = OctonionAlgebra(QQ) >>> J = JordanAlgebra(O) >>> G = J.gens() >>> G[Integer(0)] [1 0 0] [0 0 0] [0 0 0] >>> G[Integer(5)] [ 0 j 0] [-j 0 0] [ 0 0 0] >>> G[Integer(22)] [ 0 0 0] [ 0 0 k] [ 0 -k 0]
- one()[source]¶
Return multiplicative identity.
EXAMPLES:
sage: O = OctonionAlgebra(QQ) sage: J = JordanAlgebra(O) sage: J.one() [1 0 0] [0 1 0] [0 0 1] sage: all(J.one() * b == b for b in J.basis()) True
>>> from sage.all import * >>> O = OctonionAlgebra(QQ) >>> J = JordanAlgebra(O) >>> J.one() [1 0 0] [0 1 0] [0 0 1] >>> all(J.one() * b == b for b in J.basis()) True
- some_elements()[source]¶
Return some elements of
self
.EXAMPLES:
sage: O = OctonionAlgebra(QQ) sage: J = JordanAlgebra(O) sage: J.some_elements() [[6/5 0 0] [ 0 6/5 0] [ 0 0 6/5], [1 0 0] [0 1 0] [0 0 1], [0 0 0] [0 0 0] [0 0 0], [0 0 0] [0 1 0] [0 0 0], [ 0 j 0] [-j 0 0] [ 0 0 0], [ 0 0 lj] [ 0 0 0] [-lj 0 0], [ 0 0 0] [ 0 1 1/2*lj] [ 0 -1/2*lj 0], [ 1 0 j + 2*li] [ 0 1 0] [-j - 2*li 0 1], [ 1 j + lk l] [-j - lk 0 i + lj] [ -l -i - lj 0], [ 1 3/2*l 2*k] [-3/2*l 0 5/2*j] [ -2*k -5/2*j 0]] sage: O = OctonionAlgebra(GF(3)) sage: J = JordanAlgebra(O) sage: J.some_elements() [[-1 0 0] [ 0 -1 0] [ 0 0 -1], [1 0 0] [0 1 0] [0 0 1], [0 0 0] [0 0 0] [0 0 0], [0 0 0] [0 1 0] [0 0 0], [ 0 j 0] [-j 0 0] [ 0 0 0], [ 0 0 lj] [ 0 0 0] [-lj 0 0], [ 0 0 0] [ 0 1 -lj] [ 0 lj 0], [ 1 0 j - li] [ 0 1 0] [-j + li 0 1], [ 1 j + lk l] [-j - lk 0 i + lj] [ -l -i - lj 0], [ 1 0 -k] [ 0 0 j] [ k -j 0]]
>>> from sage.all import * >>> O = OctonionAlgebra(QQ) >>> J = JordanAlgebra(O) >>> J.some_elements() [[6/5 0 0] [ 0 6/5 0] [ 0 0 6/5], [1 0 0] [0 1 0] [0 0 1], [0 0 0] [0 0 0] [0 0 0], [0 0 0] [0 1 0] [0 0 0], [ 0 j 0] [-j 0 0] [ 0 0 0], [ 0 0 lj] [ 0 0 0] [-lj 0 0], [ 0 0 0] [ 0 1 1/2*lj] [ 0 -1/2*lj 0], [ 1 0 j + 2*li] [ 0 1 0] [-j - 2*li 0 1], [ 1 j + lk l] [-j - lk 0 i + lj] [ -l -i - lj 0], [ 1 3/2*l 2*k] [-3/2*l 0 5/2*j] [ -2*k -5/2*j 0]] >>> O = OctonionAlgebra(GF(Integer(3))) >>> J = JordanAlgebra(O) >>> J.some_elements() [[-1 0 0] [ 0 -1 0] [ 0 0 -1], [1 0 0] [0 1 0] [0 0 1], [0 0 0] [0 0 0] [0 0 0], [0 0 0] [0 1 0] [0 0 0], [ 0 j 0] [-j 0 0] [ 0 0 0], [ 0 0 lj] [ 0 0 0] [-lj 0 0], [ 0 0 0] [ 0 1 -lj] [ 0 lj 0], [ 1 0 j - li] [ 0 1 0] [-j + li 0 1], [ 1 j + lk l] [-j - lk 0 i + lj] [ -l -i - lj 0], [ 1 0 -k] [ 0 0 j] [ k -j 0]]
- class sage.algebras.jordan_algebra.JordanAlgebra[source]¶
Bases:
UniqueRepresentation
,Parent
A Jordan algebra.
A Jordan algebra is a magmatic algebra (over a commutative ring \(R\)) whose multiplication satisfies the following axioms:
\(xy = yx\), and
\((xy)(xx) = x(y(xx))\) (the Jordan identity).
See [Ja1971], [Ch2012], and [McC1978], for example.
These axioms imply that a Jordan algebra is power-associative and the following generalization of Jordan’s identity holds [Al1947]: \((x^m y) x^n = x^m (y x^n)\) for all \(m, n \in \ZZ_{>0}\).
Let \(A\) be an associative algebra over a ring \(R\) in which \(2\) is invertible. We construct a Jordan algebra \(A^+\) with ground set \(A\) by defining the multiplication as
\[x \circ y = \frac{xy + yx}{2}.\]Often the multiplication is written as \(x \circ y\) to avoid confusion with the product in the associative algebra \(A\). We note that if \(A\) is commutative then this reduces to the usual multiplication in \(A\).
Jordan algebras constructed in this fashion, or their subalgebras, are called special. All other Jordan algebras are called exceptional.
Jordan algebras can also be constructed from a module \(M\) over \(R\) with a symmetric bilinear form \((\cdot, \cdot) : M \times M \to R\). We begin with the module \(M^* = R \oplus M\) and define multiplication in \(M^*\) by
\[(\alpha + x) \circ (\beta + y) = \underbrace{\alpha \beta + (x,y)}_{\in R} + \underbrace{\beta x + \alpha y}_{\in M},\]where \(\alpha, \beta \in R\) and \(x,y \in M\).
INPUT:
Can be either an associative algebra \(A\) or a symmetric bilinear form given as a matrix (possibly followed by, or preceded by, a base ring argument).
EXAMPLES:
We let the base algebra \(A\) be the free algebra on 3 generators:
sage: F.<x,y,z> = FreeAlgebra(QQ) sage: J = JordanAlgebra(F); J Jordan algebra of Free Algebra on 3 generators (x, y, z) over Rational Field sage: a,b,c = map(J, F.gens()) sage: a*b 1/2*x*y + 1/2*y*x sage: b*a 1/2*x*y + 1/2*y*x
>>> from sage.all import * >>> F = FreeAlgebra(QQ, names=('x', 'y', 'z',)); (x, y, z,) = F._first_ngens(3) >>> J = JordanAlgebra(F); J Jordan algebra of Free Algebra on 3 generators (x, y, z) over Rational Field >>> a,b,c = map(J, F.gens()) >>> a*b 1/2*x*y + 1/2*y*x >>> b*a 1/2*x*y + 1/2*y*x
Jordan algebras are typically non-associative:
sage: (a*b)*c 1/4*x*y*z + 1/4*y*x*z + 1/4*z*x*y + 1/4*z*y*x sage: a*(b*c) 1/4*x*y*z + 1/4*x*z*y + 1/4*y*z*x + 1/4*z*y*x
>>> from sage.all import * >>> (a*b)*c 1/4*x*y*z + 1/4*y*x*z + 1/4*z*x*y + 1/4*z*y*x >>> a*(b*c) 1/4*x*y*z + 1/4*x*z*y + 1/4*y*z*x + 1/4*z*y*x
We check the Jordan identity:
sage: (a*b)*(a*a) == a*(b*(a*a)) True sage: x = a + c sage: y = b - 2*a sage: (x*y)*(x*x) == x*(y*(x*x)) True
>>> from sage.all import * >>> (a*b)*(a*a) == a*(b*(a*a)) True >>> x = a + c >>> y = b - Integer(2)*a >>> (x*y)*(x*x) == x*(y*(x*x)) True
Next we construct a Jordan algebra from a symmetric bilinear form:
sage: m = matrix([[-2,3],[3,4]]) sage: J.<a,b,c> = JordanAlgebra(m); J Jordan algebra over Integer Ring given by the symmetric bilinear form: [-2 3] [ 3 4] sage: a 1 + (0, 0) sage: b 0 + (1, 0) sage: x = 3*a - 2*b + c; x 3 + (-2, 1)
>>> from sage.all import * >>> m = matrix([[-Integer(2),Integer(3)],[Integer(3),Integer(4)]]) >>> J = JordanAlgebra(m, names=('a', 'b', 'c',)); (a, b, c,) = J._first_ngens(3); J Jordan algebra over Integer Ring given by the symmetric bilinear form: [-2 3] [ 3 4] >>> a 1 + (0, 0) >>> b 0 + (1, 0) >>> x = Integer(3)*a - Integer(2)*b + c; x 3 + (-2, 1)
We again show that Jordan algebras are usually non-associative:
sage: (x*b)*b -6 + (7, 0) sage: x*(b*b) -6 + (4, -2)
>>> from sage.all import * >>> (x*b)*b -6 + (7, 0) >>> x*(b*b) -6 + (4, -2)
We verify the Jordan identity:
sage: y = -a + 4*b - c sage: (x*y)*(x*x) == x*(y*(x*x)) True
>>> from sage.all import * >>> y = -a + Integer(4)*b - c >>> (x*y)*(x*x) == x*(y*(x*x)) True
The base ring, while normally inferred from the matrix, can also be explicitly specified:
sage: J.<a,b,c> = JordanAlgebra(m, QQ); J Jordan algebra over Rational Field given by the symmetric bilinear form: [-2 3] [ 3 4] sage: J.<a,b,c> = JordanAlgebra(QQ, m); J # either order work Jordan algebra over Rational Field given by the symmetric bilinear form: [-2 3] [ 3 4]
>>> from sage.all import * >>> J = JordanAlgebra(m, QQ, names=('a', 'b', 'c',)); (a, b, c,) = J._first_ngens(3); J Jordan algebra over Rational Field given by the symmetric bilinear form: [-2 3] [ 3 4] >>> J = JordanAlgebra(QQ, m, names=('a', 'b', 'c',)); (a, b, c,) = J._first_ngens(3); J # either order work Jordan algebra over Rational Field given by the symmetric bilinear form: [-2 3] [ 3 4]
REFERENCES:
- class sage.algebras.jordan_algebra.JordanAlgebraSymmetricBilinear(R, form, names=None)[source]¶
Bases:
JordanAlgebra
A Jordan algebra given by a symmetric bilinear form \(m\).
- class Element(parent, s, v)[source]¶
Bases:
AlgebraElement
An element of a Jordan algebra defined by a symmetric bilinear form.
- bar()[source]¶
Return the result of the bar involution of
self
.The bar involution \(\bar{\cdot}\) is the \(R\)-linear endomorphism of \(M^*\) defined by \(\bar{1} = 1\) and \(\bar{x} = -x\) for \(x \in M\).
EXAMPLES:
sage: m = matrix([[0,1],[1,1]]) sage: J.<a,b,c> = JordanAlgebra(m) sage: x = 4*a - b + 3*c sage: x.bar() 4 + (1, -3)
>>> from sage.all import * >>> m = matrix([[Integer(0),Integer(1)],[Integer(1),Integer(1)]]) >>> J = JordanAlgebra(m, names=('a', 'b', 'c',)); (a, b, c,) = J._first_ngens(3) >>> x = Integer(4)*a - b + Integer(3)*c >>> x.bar() 4 + (1, -3)
We check that it is an algebra morphism:
sage: y = 2*a + 2*b - c sage: x.bar() * y.bar() == (x*y).bar() True
>>> from sage.all import * >>> y = Integer(2)*a + Integer(2)*b - c >>> x.bar() * y.bar() == (x*y).bar() True
- monomial_coefficients(copy=True)[source]¶
Return a dictionary whose keys are indices of basis elements in the support of
self
and whose values are the corresponding coefficients.INPUT:
copy
– ignored
EXAMPLES:
sage: m = matrix([[0,1],[1,1]]) sage: J.<a,b,c> = JordanAlgebra(m) sage: elt = a + 2*b - c sage: elt.monomial_coefficients() {0: 1, 1: 2, 2: -1}
>>> from sage.all import * >>> m = matrix([[Integer(0),Integer(1)],[Integer(1),Integer(1)]]) >>> J = JordanAlgebra(m, names=('a', 'b', 'c',)); (a, b, c,) = J._first_ngens(3) >>> elt = a + Integer(2)*b - c >>> elt.monomial_coefficients() {0: 1, 1: 2, 2: -1}
- norm()[source]¶
Return the norm of
self
.The norm of an element \(\alpha + x \in M^*\) is given by \(n(\alpha + x) = \alpha^2 - (x, x)\).
EXAMPLES:
sage: m = matrix([[0,1],[1,1]]) sage: J.<a,b,c> = JordanAlgebra(m) sage: x = 4*a - b + 3*c; x 4 + (-1, 3) sage: x.norm() 13
>>> from sage.all import * >>> m = matrix([[Integer(0),Integer(1)],[Integer(1),Integer(1)]]) >>> J = JordanAlgebra(m, names=('a', 'b', 'c',)); (a, b, c,) = J._first_ngens(3) >>> x = Integer(4)*a - b + Integer(3)*c; x 4 + (-1, 3) >>> x.norm() 13
- trace()[source]¶
Return the trace of
self
.The trace of an element \(\alpha + x \in M^*\) is given by \(t(\alpha + x) = 2 \alpha\).
EXAMPLES:
sage: m = matrix([[0,1],[1,1]]) sage: J.<a,b,c> = JordanAlgebra(m) sage: x = 4*a - b + 3*c sage: x.trace() 8
>>> from sage.all import * >>> m = matrix([[Integer(0),Integer(1)],[Integer(1),Integer(1)]]) >>> J = JordanAlgebra(m, names=('a', 'b', 'c',)); (a, b, c,) = J._first_ngens(3) >>> x = Integer(4)*a - b + Integer(3)*c >>> x.trace() 8
- algebra_generators()[source]¶
Return a basis of
self
.The basis returned begins with the unity of \(R\) and continues with the standard basis of \(M\).
EXAMPLES:
sage: m = matrix([[0,1],[1,1]]) sage: J = JordanAlgebra(m) sage: J.basis() Family (1 + (0, 0), 0 + (1, 0), 0 + (0, 1))
>>> from sage.all import * >>> m = matrix([[Integer(0),Integer(1)],[Integer(1),Integer(1)]]) >>> J = JordanAlgebra(m) >>> J.basis() Family (1 + (0, 0), 0 + (1, 0), 0 + (0, 1))
- basis()[source]¶
Return a basis of
self
.The basis returned begins with the unity of \(R\) and continues with the standard basis of \(M\).
EXAMPLES:
sage: m = matrix([[0,1],[1,1]]) sage: J = JordanAlgebra(m) sage: J.basis() Family (1 + (0, 0), 0 + (1, 0), 0 + (0, 1))
>>> from sage.all import * >>> m = matrix([[Integer(0),Integer(1)],[Integer(1),Integer(1)]]) >>> J = JordanAlgebra(m) >>> J.basis() Family (1 + (0, 0), 0 + (1, 0), 0 + (0, 1))
- gens()[source]¶
Return the generators of
self
.EXAMPLES:
sage: m = matrix([[0,1],[1,1]]) sage: J = JordanAlgebra(m) sage: J.gens() (1 + (0, 0), 0 + (1, 0), 0 + (0, 1))
>>> from sage.all import * >>> m = matrix([[Integer(0),Integer(1)],[Integer(1),Integer(1)]]) >>> J = JordanAlgebra(m) >>> J.gens() (1 + (0, 0), 0 + (1, 0), 0 + (0, 1))
- class sage.algebras.jordan_algebra.SpecialJordanAlgebra(A, names=None)[source]¶
Bases:
JordanAlgebra
A (special) Jordan algebra \(A^+\) from an associative algebra \(A\).
- class Element(parent, x)[source]¶
Bases:
AlgebraElement
An element of a special Jordan algebra.
- monomial_coefficients(copy=True)[source]¶
Return a dictionary whose keys are indices of basis elements in the support of
self
and whose values are the corresponding coefficients.INPUT:
copy
– boolean (default:True
); ifself
is internally represented by a dictionaryd
, then make a copy ofd
; ifFalse
, then this can cause undesired behavior by mutatingd
EXAMPLES:
sage: F.<x,y,z> = FreeAlgebra(QQ) sage: J = JordanAlgebra(F) sage: a,b,c = map(J, F.gens()) sage: elt = a + 2*b - c sage: elt.monomial_coefficients() {x: 1, y: 2, z: -1}
>>> from sage.all import * >>> F = FreeAlgebra(QQ, names=('x', 'y', 'z',)); (x, y, z,) = F._first_ngens(3) >>> J = JordanAlgebra(F) >>> a,b,c = map(J, F.gens()) >>> elt = a + Integer(2)*b - c >>> elt.monomial_coefficients() {x: 1, y: 2, z: -1}
- algebra_generators()[source]¶
Return the basis of
self
.EXAMPLES:
sage: F.<x,y,z> = FreeAlgebra(QQ) sage: J = JordanAlgebra(F) sage: J.basis() Lazy family (Term map(i))_{i in Free monoid on 3 generators (x, y, z)}
>>> from sage.all import * >>> F = FreeAlgebra(QQ, names=('x', 'y', 'z',)); (x, y, z,) = F._first_ngens(3) >>> J = JordanAlgebra(F) >>> J.basis() Lazy family (Term map(i))_{i in Free monoid on 3 generators (x, y, z)}
- basis()[source]¶
Return the basis of
self
.EXAMPLES:
sage: F.<x,y,z> = FreeAlgebra(QQ) sage: J = JordanAlgebra(F) sage: J.basis() Lazy family (Term map(i))_{i in Free monoid on 3 generators (x, y, z)}
>>> from sage.all import * >>> F = FreeAlgebra(QQ, names=('x', 'y', 'z',)); (x, y, z,) = F._first_ngens(3) >>> J = JordanAlgebra(F) >>> J.basis() Lazy family (Term map(i))_{i in Free monoid on 3 generators (x, y, z)}
- gens()[source]¶
Return the generators of
self
.EXAMPLES:
sage: cat = Algebras(QQ).WithBasis().FiniteDimensional() sage: C = CombinatorialFreeModule(QQ, ['x','y','z'], category=cat) sage: J = JordanAlgebra(C) sage: J.gens() (B['x'], B['y'], B['z']) sage: F.<x,y,z> = FreeAlgebra(QQ) sage: J = JordanAlgebra(F) sage: J.gens() Traceback (most recent call last): ... NotImplementedError: infinite set
>>> from sage.all import * >>> cat = Algebras(QQ).WithBasis().FiniteDimensional() >>> C = CombinatorialFreeModule(QQ, ['x','y','z'], category=cat) >>> J = JordanAlgebra(C) >>> J.gens() (B['x'], B['y'], B['z']) >>> F = FreeAlgebra(QQ, names=('x', 'y', 'z',)); (x, y, z,) = F._first_ngens(3) >>> J = JordanAlgebra(F) >>> J.gens() Traceback (most recent call last): ... NotImplementedError: infinite set